A Pediatric Sepsis Protocol Reduced Mortality and Dysfunctions in a Brazilian Public Hospital - Medeiros, Daniela Nasu Monteiro; Mafra, Ana Carolina Cintra Nunes; Carcillo, Joseph Anthony; Troster, Eduardo Juan (Frontiers in Pediatrics, 2021)
Background: few studies in the literature discuss the benefits of compliance with sepsis bundles in hospitals in low- and middle-income countries, where resources are limited and mortality is high. Methods: This is a retrospective cohort study conducted at a public hospital in a low-income region in Brazil. We evaluated whether completion of a sepsis bundle is associated with reduced in-hospital mortality for sepsis, severe sepsis, and septic shock, as well as prevention of septic shock and organ dysfunction. Bundle compliance required the completion of three items: 1) obtaining blood count and culture, arterial or venous blood gases, and arterial or venous lactate levels; 2) antibiotic infusion within the first hour of diagnosis; and 3) infusion of 10-20 ml/kg saline solution within the first hour of diagnosis. Results: A total of 548 children with sepsis, severe sepsis or septic shock who were treated at the emergency room from February 2008 to August of 2016 were included in the study. Of those, 371 patients were included in the protocol group and had a lower median length of stay (3 days vs. 11 days; p<0.001), fewer organ dysfunctions during hospitalization (0 vs. 2; p<0.001) and a lower probability of developing septic shock. According to a propensity score analysis, mortality was lower during the post-implementation period (2.75% vs. 15.4 % (RR 95%IC 0.13 (0.06; 0.27); p <0.001)). Conclusions: a simple and low-cost protocol was feasible and yielded good results at a general hospital in a low-income region in Brazil. Protocol use resulted in decreased mortality and progression of dysfunctions and was associated with a reduced probability of developing septic shock.